ELETRIC FIELD ENHANCEMENT AND DETERIORATION OF BOILING HEAT TRANSFER AND CRITICAL HEAT FLUX IN DIELECTRIC FLUIDS - Carrica, P. M.; Masson, V. (Revista de Engenharia Térmica, 2001)
We present the results of an experimental study of the effects of externally imposed electric fields on boiling heat transfer and critical heat flux (CHF) in dielectric fluids. The study comprises the analysis of geometries that, under the effects of electric fields, cause the bubbles either to be pushed toward the heater or away from it. A local phase detection probe was used to measure the void fraction and the interfacial impact rate near the heater. It was found that the critical heat flux can be either augmented or reduced with the application of an electric field, depending on the direction of . In addition, the heat transfer can be slightly enhanced or degraded depending on the heat flux. The study of the two-phase flow in nucleate boiling, only for the case of favorable dielectrophoretic forces, reveals that the application of an electric field reduces the bubble detection time and increases the detachment frequency. It also shows that the two-phase flow characteristics of the second film boiling regime resemble more a nucleate boiling regime than a film boiling regime.